Some critical events in the geological history of eastern margin of the Bohemian Massif - Misar,Z.; Dudek,A. (Journal of the Czech Geological Society, 1993)
Demarcation of terranes, interaction of upper mantle/crust rocks and ophiolite events are discussed in the contribution. New designated terrane boundaries and reinterpreted earlier recognized faults delimit terranes of the Brunovistulicum, Moravosilesicum, Moldanubicum, Bohemicum and Lugicum. Interaction of lithospheric laminae of the upper mantle and crust representatives was in consideration of tectonometamorphic events. Ophiolite events were restricted to the Bohemicum or its equivalents in the Saxo-Thuringian zone of the Variscan Belt. Analyses of magmatic and metamorphic events and geotectonic setting of the Brunovistulicum complement the conception on geological evolution of eastern margin of the Variscan Bohemian Massif.